The Effect Of Kaliandra Honey On The Intensity Of Primary Dysmenorrhoea In Adolescent Girls At Smp 06 Diponegoro Wuluhan: The Effect Of Kaliandra Honey On The Intensity Of Primary Dysmenorrhoea In Adolescent Girls At Smp 06 Diponegoro Wuluhan - wulandari, puput (Fetus : Journal of Midwifery, 2024)
Background: Primary dysminore is caused by natural chemicals produced by thecells lining the uterine wall called prostaglandins. Prostaglandins stimulate thecontraction of the smooth muscles of the uterine wall resulting in primarydysminore. The incidence of primary dysminore in Jember Regency withadolescents aged 20-24 years is 104 people, 54.98% experience primarydysminore. An increase in prostaglandin hormones can be suppressed byflavonoid substances. Herbal ingredients that have the highest content offlavonoids to reduce menstrual pain are found in kaliandra honey.Objective:Thisstudy found out the effect of kaliandra honey on the intensity of primarydysmenorrhea in adolescent girls at SMP 06 Diponegoro Wuluhan. Methods:This study is a type of pre-experimental research with the design of one grouppretest pottest. The research sample was taken by accidental sampling so that 53adolescent girls were obtained. The statistical test uses the Wilcoxon signed ranktest. Results: Results: The intensity of pain before being given honey was mostlymoderate pain in 41 students (77.4%), after being given honey the pain intensitydropped to mild pain as many as 46 students (86.8%) and the results of theWilcoxon statistical test p = 0.000. Conclusion: There is an effect of theadministration of pure kaliandra honey on the intensity of primary dysmenorrheain adolescent girls of SMP 06 Diponegoro Wuluhan. Suggestion: This study isexpected to be developed by modifying the technique of monitoring prostaglandinlevels through certain markers with laboratory examinations, so that a morereliable level of accuracy will be obtained in determining the peak period ofdysminore.